The Specific Alteration of Gut Microbiota in Diabetic Kidney Diseases—A Systematic Review and Meta-Analysis - Wang, Yuwei; Zhao, Jin; Qin, Yunlong; Yu, Zixian; Zhang, Yumeng; Ning, Xiaoxuan; Sun, Shiren (Frontiers in Immunology, 2022)
Abstract Background: Emerging evidence indicates that gut dysbiosis is involved in the occurrence and development of diabetic kidney diseases (DKD). However, the key microbial taxa closely related to DKD have not been determined. Methods: PubMed, Web of Science, Cochrane, Chinese Biomedical Databases, China National Knowledge Internet, and Embase were searched for case-control or cross-sectional studies comparing the gut microbiota of patients with DKD and healthy controls (HC) from inception to February 8, 2022, and random/fixed-effects meta-analyses on the standardized mean difference (SMD) were performed for alpha diversity indexes between DKD and HC, and beta diversity indexes and the relative abundance of gut microbiota were extracted and summarized qualitatively. Results: A total of 16 studies (578 patients with DKD and 444 HC) were included. Compared to HC, the bacterial richness of patients with DKD was significantly decreased, and the diversity indexes were decreased but not statistically, companying with a distinct beta diversity. The relative abundance of phylum Proteobacteria, Actinomycetes and Bacteroidetes, family Coriobacteriaceae, Enterobacteriaceae and Veillonellaceae, genus Enterococcus, Citrobacter, Escherichia, Klebsiella, Akkermansia, Sutterella and Acinetobacter, and species E. coli enriched while that of phylum Firmicutes, family Lachnospiracea, genus Roseburia, Prevotella, and Bifidobacterium depleted in patients with DKD. Conclusions: The gut microbiota of patients with DKD may possess specific features characterized by expansion of genus Escherichia, Citrobacter, and Klebsiella, and depletion of Roseburia which may contribute most to the alterations of their corresponding family and phylum taxa, as well as the bacterial diversity and composition. These microbial taxa may be closely related to DKD and serve as promising targets for the management of DKD.